Centralized versus individual: Governance of farmer professional cooperatives in China - Xiangping Jia; Yamei Hu; George Hendrikse; Jikun Huanga (Leibniz Institute of Agricultural Development in Central and Eastern Europe (IAMO), 2010)
Based on a national representative survey conducted in 2009, this study shows that the decision-making within Farmer Professional Cooperatives (FPCs) in China is decentralized to individual farmers. However, there is a trend that the decision rights of farming are decomposed to marketing, production and input procuring. While the rights for production and input procuring stay with family farmers, marketing rights tend to be collectivized. Compared to FPCs having external initiating sources, FPCs initiated by farmers are more inclined to introduce centralized decision-making. The governance structure of FPCs in transition China presents hybrid forms of both hierarchy and family farming.
Keywords: L14; Q13; Q18; 330; Farmer; Cooperatives; Governance; China